Utilization of Integrated Digital Cashier for Business Sustainability in Kampung Nila, Kawali Village, Ciamis Regency - Octaviana Helbawanti; Abdul Mutolib; Riantin Hikmah Widi; Lidya Nur Amalia; Ati Rosliyati; Candra Nuraini (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
ABSTRACT The Bojongsari Fish Processing and Marketing Group (Poklahsar) in Kampung Nila encountered primary challenges in managing the inventory of perishable fishery products and in financial management, which still relied on manual record-keeping. Manual systems were at risk of data loss, inaccurate calculations, and a lack of transparency, which negatively impacted the group’s accountability and business sustainability. The community service activity aimed to strengthen business governance and ensure the group’s business sustainability through inventory management, sales, and simple financial record-keeping; practical skills in basic financial reporting; and operating an integrated digital cash register. The outreach methods used in the activity included presentations on inventory and financial management; practical demonstrations of digital cash register applications; interactive discussions on operational procedures and coordination of price and stock changes; and an assessment of interest in transitioning from manual to digital record-keeping. The implementation of integrated digital cash registers enabled partners to acquire technical skills in inventory management, transaction record-keeping, and the preparation of simplified financial reports. Service delivery improved and the group's financial transparency became easily accessible. The implementation of digital cash registers fostered a collective awareness of the importance of financial and inventory management for the sustainability of community-based businesses. Partners adopted digital cash registers for daily sales activities in Kampung Nila as well as for product exhibitions outside of Kampung Nila. As a result, digital cash registers were accessible to all product sales channels in Kampung Nila Keywords: Kampung Nila, Inventory Management, Digital Cash Registers, Community Empowerment, Simple Financial Reporting